A cross-sectional study to examine factors associated with primary health care service utilization among older adults in the Irbid Governorate of Jordan - Alkhawaldeh, A.; Holm, M.; Qaddumi, J.; Petro, W.; Jaghbir, M.; Al Omari, Omar (Hindawi Publishing Corporation, 2014)
Background: Recently, the percentage of older adults in developing countries has increased significantly. Objective: This study examined patterns and factors associated with primary health care services utilization in the past 1, 6, and 12 months. Method: A cross-sectional study design was used to collect data from 190 older adults in the Irbid governorate of Jordan. Results: Primary health care services were used by less than half of the participants in the past 1 month, by 68.4% in the past 6 months, and by 73.8% in the past 12 months. Primary health care (PHC) services use was associated with age, education level, tobacco use, chronic illnesses, perceived general health status today, a physical component summary score, employment, and perceived general health status in the past 6 and 12 months. The primary predictor of PHC services use at 1, 6, and 12 months was chronic illnesses (OR = 13.32), (OR = 19.63), and (OR = 17.91), respectively. Conclusion: Although many factors were associated with PHC service utilization, the strongest predictor of PHC service utilization was chronic illnesses.